Influência da estrutura de estanhossílicas mesoporosas na isomerização da glicose - Lorenti, Juliana Pimenta (2020)
The use of biomass in order to obtain chemicals and fuels that can substitute the fossil matrix has been investigated and treated with high interest. This way, the research in catalysis becomes essential to overpass barriers and to consolidate the use of such renewable sources. Tin silicas have been showed as a promisor candidates in glucose to fructose isomerization, given the fact the last hexose is very interesting regarding its conversion to HMF, a platform molecule with a high potential to substitute monomers obtained from fossil fuels. Therefore, this work has as objective to synthesize water-resistant catalysts, with Lewis acidity properties, high concentration of silanol groups and a high pore diameter, as a way of surpassing the limitations imposed by the Sn-Beta zeolite, which is the most studied catalyst for the isomerization reaction. This way, the effect of the synthesis parameters on Sn-MCM-41 and Sn-SBA-15 will be investigated. Furthermore, we seek to understand, by synthetizing Sn-MCM-48 and Sn-SBA-16, how the change in the mesoporous’ structures (M41S and SBA) influences the catalysts’ properties, in a way that the main goal is to suit the catalytic properties with the structural and textural properties. Increasing the acid concentration and the Sn loading led to a bimodal distribution of the unit cell parameter for the Sn-SBA-15, while for the Sn-MCM-48, the increase in the last parameter to 4,5% prevented the ordered formation of such material. Thus, the best synthesis parameters for the formation of a well-organized structure were 3,0% Sn for both Sn-SBA-15 and Sn-MCM-48 materials, and 0,049 mol L-1 for Sn-SBA-15. It was observed a good structural ordainment for the Sn-MCM-41 materials synthetized with NH4OH, while the same was not observed for the ones synthetized with TMAOH. The superficial area and the microporosity formation were not significantly affected by the synthesis parameters among the materials, but they were actually affected by the different scaffolds studied. A study regarding the catalytic activity of Sn-SBA-15 showed that the reaction depended on the identity of the solvent used, in a way that the initial TOF for fructose formation increased in the following order: methanol<THF<GVL. These mesoporous Sn-silicas were employed in the glucose conversion reaction, being Sn-MCM-41 the most selective for fructose (74%), followed by Sn-SBA-16 (72%). The Sn-MCM-48 presented low selectivity for fructose (31%), because they also produced mannose with a similar selectivity (19%), mostly due to the presence of K+ cations, which favor the reaction pathway towards manose formation. Combining these mesoporous silicas with HCl allowed the direct conversion of glucose in 5-hydroxmethylfurfural and, in this case, Sn-MCM-41 reached the highest selectivity (70%).